The new international legal order and new states in the Balkans - Dimitrijević Duško (Međunarodni Problemi)
In this study the author attaches a great importance to the theoretical examination of the concept of the New International Legal Order that was embodied in the last decades of the 20th century. The starting point for that reflection is the dissolution of the SFR Yugoslavia that illustrates one of the fundamental legal precedents. Reminding that the basic principle for the post-modern State behavior must be the one that includes minimal disturbance of the existing international legal relations, the author stresses that "the Yugoslav case" was customized in the way to respond to the new reality where the principle of effectiveness played an essential role in valuation of the statehood. It could also be one of the greatest catalysts for all further 'development rules' of international law.